PENGARUH PELATIHAN DAN KOMITMEN ORGANISASI TERHADAP KUALITAS LAYANAN PADA STAF OPERASIONAL DI HOTEL AMNAYA RESORT KUTA - Ni Putu Putri Cyntia Dewi (Universitas Pendidikan Ganesha, 2026)
The tourism industry is a strategic sector of Indonesia's economy, particularly in Bali. In the highly competitive hospitality landscape, service quality determines guest satisfaction and loyalty. This study aims to examine and analyze the effect of training and organizational commitment on the service quality of operational staff at Amnaya Resort Kuta Hotel. This quantitative research adopts a descriptive-correlational design with a saturated sample of 106 operational staff across various departments. Data were collected using a 5-point Likert scale questionnaire, thoroughly tested for validity and reliability. The collected data were analyzed using multiple linear regression and ensured to be free from classic assumption pathologies. The t-test results indicate that training has a positive and significant effect on service quality (T hitung 9,234 > t tavel 1,983 ; Sig. <0,001 ). Organizational commitment also positively and significantly affects service quality ( t hitung 4,058 > t tabel 1,983; Sig. < 0,001 ).Simultaneous testing (F-test) proves that training and organizational commitment collectively influence service quality ( F hitung 132,567 ; Sig. 0,001). The coefficient of determination (R2) is 0.720, indicating that 72% of service quality variation is determined by these variables. In conclusion, improving service quality can be optimally achieved through effective training programs and strong affective employee commitment.